STAR Technique in the ABCD5E Learning Model to Improve Teacher Assessment Capability in Early Chilhood Education - Handayani, Sri Wiji; Pranoto, Yuli Kurniawati Sugiyo; Puspitaningrum, Setiarif; Ghazali, Muhammad Nur Azam Bin (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Assessment is an inseparable part of the learning process. However, teachers in the ABCD5E learning model do not conduct assessments optimally. In the results of discussions and questionnaires, more than 65% found it difficult to conduct assessments. This encourages the creators of the ABCD5E learning model to find techniques to make it easier for PAUD teachers to conduct assessments with the ABCD5E learning model. The creator of the ABCD5E learning model adopted the STAR technique from DDI. The purpose of this research is to determine the effectiveness of the STAR Technique (Situation, Task, Action, and Result) in learning with the ABCD5E model to improve PAUD teachers' assessment skills. The research method used was experimental, using a Pretest-Posttest Control Group Design. The results showed an increase in the ability of teachers to conduct assessments using the STAR technique in the implementation of the ABCD5E learning model.